Large-Scale Phenotyping of an Accurate Genetic Mouse Model of JNCL Identifies Novel Early Pathology Outside the Central Nervous System - Staropoli, John F.; Haliw, Larissa; Biswas, Sunita; Garrett, Lillian; Hölter, Sabine M.; Becker, Lore; Skosyrski, Sergej; Da Silva-Buttkus, Patricia; Calzada-Wack, Julia; Neff, Frauke; Rathkolb, Birgit; Rozman, Jan; et al. (PLOS ONE, 2012)
Cln3Δex7/8 mice harbor the most common genetic defect causing juvenile neuronal ceroid lipofuscinosis (JNCL), an autosomal recessive disease involving seizures, visual, motor and cognitive decline, and premature death. Here, to more thoroughly investigate the manifestations of the common JNCL mutation, we performed a broad phenotyping study of Cln3Δex7/8 mice. Homozygous Cln3Δex7/8 mice, congenic on a C57BL/6N background, displayed subtle deficits in sensory and motor tasks at 10–14 weeks of age. Homozygous Cln3Δex7/8 mice also displayed electroretinographic changes reflecting cone function deficits past 5 months of age and a progressive decline of retinal post-receptoral function. Metabolic analysis revealed increases in rectal body temperature and minimum oxygen consumption in 12–13 week old homozygous Cln3Δex7/8mice, which were also seen to a lesser extent in heterozygous Cln3Δex7/8 mice. Heart weight was slightly increased at 20 weeks of age, but no significant differences were observed in cardiac function in young adults. In a comprehensive blood analysis at 15–16 weeks of age, serum ferritin concentrations, mean corpuscular volume of red blood cells (MCV), and reticulocyte counts were reproducibly increased in homozygous Cln3Δex7/8 mice, and male homozygotes had a relative T-cell deficiency, suggesting alterations in hematopoiesis. Finally, consistent with findings in JNCL patients, vacuolated peripheral blood lymphocytes were observed in homozygous Cln3Δex7/8 neonates, and to a greater extent in older animals. Early onset, severe vacuolation in clear cells of the epididymis of male homozygous Cln3Δex7/8 mice was also observed. These data highlight additional organ systems in which to study CLN3 function, and early phenotypes have been established in homozygous Cln3Δex7/8 mice that merit further study for JNCL biomarker development.